Gasification of Psidium guajava L. Waste Using Supercritical Water: Evaluation of Feed Ratio and Moderate Temperatures - Sandro González-Arias; Abel Zúñiga-Moreno; Ricardo García-Morales; Octavio Elizalde-Solis; Francisco J. Verónico-Sánchez; Sergio O. Flores-Valle (Energies, 2021)
Biomass waste, as raw material for renewable energy, is an attractive alternative since it does not compete with human food supply. An emerging alternative for its treatment is supercritical water gasification (SCWG), due to the high moisture content of some types of biomass. On this regards, guava fruit (Psidium guajava L.) is one of the most wasted agro-food products in Mexico. This motivated us to evaluate gasification of guava waste on dry biomass base under supercritical water conditions for the first time, with the aim of analyzing the impact of moderate temperatures and feed ratios as reaction parameters on gas products. Temperature was varied in the range of 673.15–773.15 K and using a batch reactor loaded with biomass:water (B:W) mass ratios of 1:1, 1:4, and 1:6. Furthermore, the obtained solid, liquid, and gas phase products were characterized. Hydrogen (H2), carbon dioxide (CO2), carbon monoxide (CO), methane (CH4), ethane (C2H6), propane (C3H8), and butane (C4H10) were identified in gas phase and quantified by means of a gas chromatograph equipped with a TCD detector. Liquid and solid phase products were subjected to Fourier Transform Infrared spectroscopy analyses. This preliminary research indicated that high temperature operation and high biomass:water mass ratio enhanced gas yields (mol/kg) of about 4.137 for CH4, 6.705 for CO2, and 7.743 for H2; whereas the selectivity and gas efficiency for hydrogen was 65.26% and 58.94%, respectively.